Mother Earth, Mother Africa and Theology - Dreyer, Yolanda (HTS Religion & Society Series, 2021)
The theological role of African women and men in sustainable development and environmental justice strongly emerges in this book. Picking up the theme and metaphor of the fifth pan-African conference of the Circle of Concerned African Women Theologians (hereafter 'Circle'), 'Mother Earth and Mother Africa', this book titled Mother Earth, Mother Africa and Theology presents original and innovative research by scholarly members and friends of the Circle. The main contribution of the volume is its multi- and trans-disciplinary exploration and reimagining of human relationships to Earth from an African ecofeminist and ecowomanist theological perspective. It engages in critical conversations of re-interpreting and re-imagining African cultural, religious, theological, and philosophical perspectives on gender and the Earth. The aim is to construct Earth-friendly relationships in the face of the growing global environmental crisis. Scholarly voices of African women and men from fields such as Theology, Environmental Law and Policy, Tourism, Agricultural Science and Natural Resources, and Economics are reflected in this book, which consists of three parts: Creation, the Trinity, and Mother Africa; Caring for Mother Africa; and Mother Africa and her daughters' (in)fertility. Each of the eleven chapters in the volume presents the metaphor of Mother Earth, Mother Africa, and gender relations, with the aim to explore life-affirming, life-enhancing human relationships to Earth from the author's particular area of specialisation and context.